Performance of Some Tree Species in Alkali Soil - Naldu, C. V.; Srinivasa Sastry, P. S.; Srivasuki, K. P. (Indian Forester, 1999)
Tree species performance trial was conducted on alkali soils with five tropical species. All the five tree species namely Acacia ferruginea, Albizia lebbek, Azadirachta indica, Emblica officinalis and Pongamia pinnata were found to grow well in alkali soils having the values of pH 9.4, ESP 33, Ece 8.1 dsm-1, CaCO3 5.7%. Among the five tropical tree species studied, maximum total biomass production (leaf, small branches, stem and root) was observed in Acacia ferruginea and minimum in Emblica officinalis. High survival percentage (69-93%) in all the tree species showed better prospective for wastelands afforesiation and social forestry programmes to meet the energy demand as well as to maintain ecological balance and environmental stability.